Human health risk assessment of lead emission from antropohen sources - Agapova, V. T.; Zolot′ko, E. V. (Science and Transport Progress, 2012)
It was investigated intensity of lead environmental population in zone of battery production, determined the individual and population carcinogenic and non- carcinogenic risk characteristics of inhalation and oral admission of lead in human body.